Which news moves the euro area bond market? - Andersson, M.; Overby, L. J.; Sebestyén, S. (German Economic Review, 2010)
This paper explores a long dataset (1999-2005) of intraday prices on German long-term bond futures and examines market responses to major macroeconomic announcements and ECB monetary policy releases. German bond markets tend to react more strongly to the surprise component in US macro releases compared with aggregated and national euro area and UK releases, and the strength of those reactions to US releases has increased over the period considered. We also document that the numbers of German unemployed workers consistently have been known to investors before official releases.